Using simulation training to facilitate moving to a new neonatal unit. (7th June 2011) - Arif, T; Sood, A; Cusack, J; Fawke, J
Abstract : Introduction: A multi-disciplinary, high fidelity neonatal simulation training programme is well established in the Leicester Neonatal Service. We present the use of simulation training to facilitate relocation to a new neonatal unit. Methods: Four simulation sessions were held 2 weeks prior to relocation into a new Neonatal Unit. Each involved junior (ST1-3) and senior (ST4+) medical and nursing staff. Format: introduction (15 min), simulated scenario (20 min), a group debrief (30 min) and completion of an evaluation form. Qualitative thematic analysis was performed based on observation and feedback from the debriefing sessions and questionnaires. The simulated scenario used two high fidelity mannequins to simulate two emergencies: Neonatal ITU: managing a cyanosed baby in an environment unfamiliar to them. Neonatal Nursery: An emergency alarm was triggered for the team to recognize, locate and respond to. The team had to manage an apnoeic baby using the equipment available. Results: Staff identified learning points included cot space orientation, equipment location and familiarisation, emergency call systems, unit geography. Uncertainties over team dynamics and responsibilities were exposed. Important latent hazards were identified in all sessions particularly around using the new NeoPuff system. Conclusions: Simulation facilitated relocation to a new neonatal unit by educating staff about the location of important clinical areas and the functioning of new equipment. Potentially life threatening latent hazards were identified before they manifest themselves. Individual and managerial awareness of issues that may hinder relocation and acclimatization to the new unit was raised.